PROSES PENGOLAHAN TERI NASI (Stolephorus commersonii) Di PT. DWI BINA UTAMA (DBU) DUSUN KALIASIN DESA TANJUNG PECINAN KECAMATAN MANGARAN, KABUPATEN SITUBONDO - Ika Junianingsih; Ramli Ramli (Faculty of Science and Technology University Ibrahimy, 2013)
Stolephurus commersonii is one of fishery products into the non-oil export commodities that are being developed, so it needs to be a good handling or processing, so that it can also be S. commersonii consumed in areas far from producing regions. In marketing, S. commersonii can be found in the form of fresh fish and in the form of processed fish. The purpose of research is to explain about the processing of S. commersonii). From the results of this study was able to conclude that the raw material in the production of rice in the company anchovies are stolep Horus commersonil in wet form (Raw Material). While food additives used are salt (NaCl) and supporting material in the form of water and ice. The production process consists of rice teri receipt of raw materials. Washing, boiling, draining, drying, sorting, sizing, packaging, cold storage in cold storage.